2013
DOI: 10.1016/j.vetpar.2013.05.006
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis of fasciolosis in feces of sheep by means of a PCR and its application in the detection of anthelmintic resistance in sheep flocks naturally infected

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…More recently these researchers compared these three techniques for use in the detection of fluke drug resistance in sheep (Robles-Pérez et al, 2013), finding PCR to be the most sensitive. However the authors used the coproantigen ELISA kit manufacturer’s recommendations of an optical density of 0.15 as the cut-off value for positivity.…”
Section: Discussionmentioning
confidence: 99%
“…More recently these researchers compared these three techniques for use in the detection of fluke drug resistance in sheep (Robles-Pérez et al, 2013), finding PCR to be the most sensitive. However the authors used the coproantigen ELISA kit manufacturer’s recommendations of an optical density of 0.15 as the cut-off value for positivity.…”
Section: Discussionmentioning
confidence: 99%
“…Martínez‐Pérez, Robles‐Pérez, Rojo‐Vázquez, and Martínez‐Valladares () developed a nested‐PCR capable of detecting the infection in faeces of sheep as early as 2 wpi by amplifying a 423 bp fragment of the cytochrome C oxidase 1 gene. Robles‐Pérez, Martínez‐Pérez, Rojo‐Vázquez, and Martínez‐Valladares () also detected the infection at 2 wpi but by a conventional PCR, which is a less time consuming method, and amplifying a 292 bp fragment of the ITS2 gene. Ayaz, Ullah, AbdEl‐Salam, Shams, and Niaz () compared the prevalence of F. hepatica in cattle and buffaloes using the FEC and a PCR method; authors showed the higher sensitivity of the molecular technique.…”
Section: Diagnosismentioning
confidence: 99%
“…Mart ınez-Valladares and Rojo-V azquez (2016) developed a LAMP assay to detect fluke DNA in faeces of sheep and compared the results with a conventional PCR. Detection of infection was confirmed during the first wpi by both techniques, and in naturally infected sheep, the sensitivity was slightly higher with the LAMP Indeed, in the study by Mart ınez-Valladares and Rojo-V azquez (2016), samples were subjected to ethanol precipitation after the DNA extraction, following the protocol described byRobles- P erez et al (2013), to concentrate and purify the samples.With the exception of the LAMP assay, all the diagnostic tests described for fluke infection require laboratory facilities. This extends the time taken to get results back to farmers and also increases cost.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Analysis of fluke infections in cattle in Queensland showed prevalence ranging from 0.4 to over 50% (Roberts, 1982;Baldock and Arthur, 1985;Molloy and Anderson, 2006). Since the 1980s control of fasciolosis in Australia has relied on the use of Triclabendazole (TCBZ) (Boray et al, 1983) but resistance to this drench, first reported in Victoria (Overend and Bowen, 1995), has now been identified in livestock in south-eastern Australia (Brockwell et al, 2014), the United Kingdom, Europe and South America (Alvarez-Sanchez et al, 2006;Daniel et al, 2012;Gordon et al, 2012;Sargison, 2012;Ortiz et al, 2013;Robles-Pérez et al, 2013). Burdens of drug-resistant flukes of 20-34 were observed in cattle following treatment with TCBZ in Australia (Brockwell et al, 2014).…”
Section: Introductionmentioning
confidence: 99%